ChemInform Abstract: Direct Conversion of Aromatic Aldehydes into Benzamides via Oxidation with Potassium Permanganate in Liquid Ammonia. Issue 22 (15th May 2015) - Antoniak, Damian; Sakowicz, Arkadiusz; Loska, Rafal; Makosza, Mieczyslaw
Abstract: The scope of the title reaction may be limited by the formation of the corresponding carboxylic acid as a side product.